100 pengetahuan tentang serangga dan laba-laba / Steve Parker ; alih bahasa, Indriyati Wibisono ; penyunting, Rudiyanto - PARKER, Stave; Wibisono, Indriyah; Rudiyanto (Pakar Raya, 2005)
48 hlm ilus 29 cm